Provisional Application of Treaties. From the Vienna Convention to the UN ILC Guide and Beyond - Mik, Cezary (Polish Review of International and European Law, 2022)
The article is devoted to the provisional application of treaties (PATs) as it was given by the Vienna Convention on the Law of Treaties, as well as that which results from further development of this legal institution, especially from the work of the International Law Commission and legal practice. In particular, the elements comprising the PATs mechanism, its place in the field of incurring international obligations, the legal effects of the PATs, the scope of the PATs, as well as the relation to other provisions of the Vienna Convention, and finally the use of the PATs during armed conflicts are critically analyzed. The pragmatic nature of the PATs is highlighted. The differences between the provisional application of the treaty and the situation when it has entered into force are shown. It is considered that PATs can be seen as one of the manifestations of the deformalization of international law, reducing the importance of formal consent to be bound by a treaty. The dangers of the temporality ex definitione produced by the PATs were also pointed out.